Structural optimization of 3D printed hdyroxyapatite scaffolds - Isaacson, Nelson D., author; Prawel, David, advisor; James, Susan, committee member; Séguin, Bernard, committee member (Colorado State University. Libraries, 2021)
Poor healing of critically sized bone defects affects 1.5 million Americans per year and results in more than $1 billion in treatment and therapy cost. Treatment options remain limited and often lead to reoperations, clinical complications, poor functional outcomes, and limb loss, making this one of the biggest challenges in orthopedic medicine, resulting in significant personal and economic cost. Healing strategies using autografts, allografts and xenografts are limited by shortage of available tissue and failure to heal, with complication rates of 50% from delayed or non-union, 30% from allograft fracture, and 15% from infection. Decades of research has been dedicated to solving this problem using a wide variety of bone regeneration techniques. Tissue engineered solutions have emerged that deploy biodegradable, osteoconductive scaffolds to provide structural support and osteoinductive stimulus, with suitable porosity to enable nutrient and waste exchange and angiogenesis. Promising calcium phosphate biomaterials like hydroxyapatite (HAp) and β-tricalcium phosphate are widely studied for bone regeneration scaffolds due to their excellent bioactivity (osteoinductivity, osteoconductivity and osseointegration), mineral composition and tunable degradation rates. Advanced scaffold topologies such as a type of triply periodic minimal surface (TPMS) structure called gyroids are yielding scaffolds that are stiffer and stronger than traditional rectilinear scaffold topologies. Gyroids are ideal candidates for scaffold designs due to their relatively high mechanical energy absorption and robustness, interconnected internal porous structure, scalable unit cell topology, and smooth internal surfaces with relatively high surface area per volume. In our study, a method of layer-wise, photopolymerized viscous extrusion, a type of additive manufacturing, was used to fabricate HAp gyroid scaffolds with 60%, 70% and 80% porosities. Our study is the first to use this method to produce and evaluate calcium-phosphate-based scaffolds. Gyroid topology was selected due to its interconnected porosity and superior, isotropic mechanical properties compared to typical rectilinear lattice structures. Our 3D printed scaffolds were mechanically tested in compression and examined to determine the relationship between porosity, ultimate compressive strength, and fracture behavior. Compressive strength increased with decreasing porosity. Ultimate compressive strengths of the 60% and 70% porous gyroids are comparable to that of human cancellous bone, and higher than previously reported for rectilinear scaffolds of the same material. Our gyroid scaffolds exhibited ultimate compressive strength increases between 1.5 and 6.5 times greater than expected, based on volume of material, as porosity decreased. The Weibull moduli, a measure of failure predictability, were predictive of failure mode and found to be in the accepted range for engineering ceramics. The gyroid scaffolds were also found to be self-reinforcing such that initial failures due to minor manufacturing inconsistencies did not appear to be the primary cause of premature failure of the scaffold. The porous gyroids exhibited scaffold failure characteristics that varied with porosity, ranging from monolithic failure to layer-by-layer failure, and demonstrated self-reinforcement in each porosity tested.
Keywords: gyroid; porosity; scaffold; mechanical testing; additive manufacturing; robocasting